Biomarker results from the eastern Fram Strait between 40 and 33.5 ka b2k - Wanyee Wong; Bjørg Risebrobakken; Malin Ödalen; Amandine Tisserand; Kirsten Fahl; Ruediger Stein; Eystein Jansen (PANGAEA, 2025)
We present a biomarker dataset from marine sediment core MD99-2304, retrieved from the eastern Fram Strait (77°37 extquotesingle15.6N, 9°56 extquotesingle54E) at a water depth of 1348 m. The core was collected using a piston corer during the Marion Dufresne IMAGES 5 expedition (leg MD114) in 1999. This dataset provides sea ice extent in the eastern Fram Strait between 40 and 33.5 ka b2k, covering a period within Marine Isotope Stage 3 (MIS 3). With a temporal resolution of 20–40 years per sample, it contributes to the mechanical understanding of abrupt climate change during Dansgaard-Oeschger (D-O) events. The biomarker analysis was conducted at the Alfred Wegener Institute (AWI), Germany, in 2022 and 2023. The measured biomarkers include Total Organic Carbon (TOC) (%), Highly Branched Isoprenoids (HBIs) IP25, HBI diene, HBI-III (Z-isomer), and HBI III (E-isomer), and the sterols brassicasterol, dinosterol, campesterol, and sitosterol (μg/TOC). Biomarker measurements were performed using an Agilent 7890B Gas Chromatograph (GC) equipped with a 30 m DB-1MS column (0.25 mm i.d., 0.25 μm film thickness) and coupled to an Agilent 5977A mass selective detector (MSD, 70 eV constant ionization potential, Scan 50–550 m/z, 1 scan/s, ion source temperature 230°C, Performance Turbo Pump), with selected ion monitoring mode (SIM) for HBIs and full scan mode (50-550 m/Z) for sterols. The balance factors (c) for PIP25 indices are 2.82 for PIIIIP25 (IP25-HBI-III (Z)), 0.025 for PBIP25 (IP25-brassicasterol), and 0.044 for PDIP25 (IP25-dinosterol). TOC measurement was conducted using a Leco CS-125 Carbon-Sulfur Analyzer. The age model of MD99-2304 is established by tuning low field magnetic susceptibility to the magnetic susceptibility of Core MD95-2010 from the Norwegian Sea (Kissel et al., 1999); updated in Sadatzki et al. (2020), and the age model of MD95-2010 was tied to the chronology of MD99-2284 (Berben et al., 2020). The age model for MD99-2304 was established by tuning its low-field magnetic susceptibility to that of core MD95-2010 from the Norwegian Sea (Kissel et al., 1999; Sadatzki et al., 2020). The chronology of MD95-2010 was further tied to core MD99-2284 (Berben et al., 2020), ensuring a robust age framework for the dataset.